Harmonization of Hard and Soft Power Approaches in Anti-Terrorism Policy: Lessons from Poso Regency - Imam Hanafi; Fitriani Abdullah (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
This research examines the harmonization of hard power and soft power approaches in counter-terrorism policy implementation within Poso Regency, Central Sulawesi. Using Dunn and Ripley's evaluation framework, this study analyzes the effectiveness of Operation Madago Raya as a manifestation of Indonesia's evolving counter-terrorism strategy. The research employs an interpretive methodology with qualitative data collection involving six key informants over a three-month period. Data analysis encompasses policy impact measurement, compliance assessment, explanatory analysis, information acquisition, feedback mechanisms, and audit implementation. Results demonstrate significant achievements in integrating enforcement capabilities with community empowerment programs. Statistical evidence shows a 70 percent reduction in terrorist activities, 90 percent compliance with operational protocols, and 80 percent accuracy in information processing systems. The study reveals that effective counter-terrorism requires comprehensive approaches that address both immediate security threats and underlying socio-economic factors contributing to radicalization. The Poso experience provides valuable insights for developing adaptive governance frameworks that balance security imperatives with community engagement. Key findings emphasize the importance of technological modernization, personnel capacity enhancement, and sustained community participation in achieving sustainable counter-terrorism outcomes. This research contributes to understanding policy effectiveness in complex post-conflict environments and offers strategic recommendations for replicating integrated approaches in similar regional contexts.